Carbon nano-tube and carbon nano-tube resin composition

JP2025029481APending Publication Date: 2025-03-06DR GOO

Patent Information

Application Number
JP2023134185
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-03-06

AI Technical Summary

Benefits of technology

【0010】 本発明の一態様によれば、金属不純物を低減でき、かつ、分散性に優れているカーボンナノチューブ、並びに、カーボンナノチューブ樹脂組成物を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029481000002
    Figure 2025029481000002
  • Figure 2025029481000001
    Figure 2025029481000001
Patent Text Reader

Abstract

To provide a carbon nano-tube that can reduce metallic impurities and have excellent dispersibility.SOLUTION: A carbon nano-tube is subjected to graphitization treatment and then pulverization treatment to have a particle size D50 of 100 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to carbon nanotubes (hereinafter sometimes referred to as CNTs) and a carbon nanotube resin composition. [Background technology]

[0002] Currently, lithium-ion secondary batteries (hereinafter sometimes referred to as Lib) are used in mobile phones, laptops, digital cameras, and automobiles (e.g. EV, HEV, P-HEV), and are making a great contribution to improving the productivity of various industries and the quality of life. The electrodes of Lib are formed from a positive electrode in which an electrode mixture consisting of a positive electrode active material containing lithium ions, a conductive additive, and an organic binder is fixed to a metal foil current collector, and a negative electrode in which an electrode mixture consisting of a negative electrode material that can insert and remove lithium ions, a conductive additive, and an organic binder is fixed to the surface of a metal foil assembly.

[0003] Usually, lithium transition metal composite oxides such as lithium cobalt oxide are used as the positive electrode material, but these have low electronic conductivity and sufficient battery performance cannot be obtained when used alone. Therefore, carbon black (hereinafter sometimes referred to as CB), especially acetylene black or ketjen black, is added as a conductive additive to improve the conductivity and reduce the internal resistance of the electrode. On the other hand, graphite is usually used as the negative electrode active material, but improvements are being made every day, such as adding CB as a conductive additive to improve charge and discharge characteristics. However, the Lib industry and its users are demanding even higher performance products, such as higher capacity, higher safety, and reduced cycle deterioration caused by repeated charging and discharging.

[0004] As a measure to meet this demand, improvements have been attempted, such as blending CNT with conventional CB or using CNT alone, especially as a conductive assistant for the positive electrode. For example, Non-Patent Document 1 reports that as a result of a system in which acetylene black is blended with CNT at a ratio of 100:1, "CNT acts like a conductive binder, lowering the initial resistivity, improving the binding strength, mitigating the breakage of acetylene black due to expansion and contraction during charging and discharging, and greatly improving the cycle characteristics." The use of CNT in LIBs has spread rapidly based on these many achievements, and they are now widely used in LIBs for automobiles. On the other hand, it is true that Japanese Lib manufacturers, in particular, are requesting material manufacturers to provide a guarantee of "10 years, 100,000 km." Among materials, the metal catalyst contained in CNT is particularly problematic.

[0005] There are two methods for manufacturing multi-walled CNTs: chemical vapor deposition and physical vapor deposition. Chemical vapor deposition is suitable for mass production because it is relatively easy to scale up the reactor. Chemical vapor deposition can be broadly divided into two methods. One is a method in which a catalyst such as a metal compound or a co-catalyst such as sulfur is dissolved in a hydrocarbon such as benzene, and hydrogen is supplied as a carrier gas to a reactor at 1000°C or higher to generate the catalyst and grow CNTs on the spot (floating catalyst method). The other is a method in which a pre-prepared supported catalyst is placed in a reactor heated to 500°C to 700°C, and a mixture of hydrocarbons such as ethylene and hydrogen and nitrogen is supplied to react with each other (supported catalyst method). Most of the multi-walled CNTs currently on the market are made using the supported catalyst method. CNTs obtained by the supported catalyst method are free of pyrolytic carbon deposition due to the self-decomposition reaction of hydrocarbons and are relatively highly crystalline, so there is no need to carry out heat treatment for graphitization, which is essential for the floating catalyst method.However, since no heat treatment for graphitization is carried out, usually about 3 to 6% of the catalytic metal remains in the CNTs obtained by the supported catalyst method.

[0006] When CNTs containing metal impurities are used as a conductive additive for the positive electrode, the positive electrode is in an oxidizing atmosphere, so transition metals such as iron or cobalt may be oxidized and dissolved. In addition, when CNTs containing metal impurities are used for the negative electrode, metal deposition may occur. In the worst case, the eluted or precipitated metal may break the separator membrane, resulting in an internal short circuit. Furthermore, even if these metal impurities are initially tiny, the deposits may grow large and break the separator as the battery is used. In order to create a safe LIB that is free of internal short circuits and does not cause partial heat generation or deterioration, it has become important to reduce the metal impurities of the CNTs used as conductive additives as much as possible and to use CNTs with excellent dispersibility. [Prior art documents] [Non-patent literature]

[0007] [Non-Patent Document 1] "Toyama Prefectural Industrial Technology Center Research Report No. 29 (2015)", published by Toyama Prefectural Industrial Technology Center, pp. 97-98 Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide carbon nanotubes that can reduce metal impurities and have excellent dispersibility, and a carbon nanotube resin composition. [Means for solving the problem]

[0009] According to the present invention, there are provided a carbon material granule, a method for producing a carbon material granule, and a conductive resin composition, which are described below. [1] Carbon nanotubes that have been subjected to a graphitization process and then a crushing process, The particle diameter D of the carbon nanotube 50 is 100 μm or less, Carbon nanotubes. [2] Carbon nanotubes that have been pulverized into carbon nanotube powder or carbon nanotube granules are graphitized. Carbon nanotubes. [3] The carbon nanotube according to [2], The particle diameter D of the carbon nanotube 50 is 100 μm or less, Carbon nanotubes. [4] A composition comprising the carbon nanotubes according to any one of [1] to [3] and a binder resin. Carbon nanotube resin composition. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide carbon nanotubes and a carbon nanotube resin composition that can reduce metal impurities and have excellent dispersibility. [Brief description of the drawings]

[0011] [Figure 1] 1 is a photograph showing dispersibility in the resin compositions obtained in Examples 1 to 5, Comparative Examples 1 to 3, and Reference Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0013] [Carbon nanotubes] First, the carbon nanotube according to this embodiment will be described. The carbon nanotubes according to this embodiment are carbon nanotubes that have been subjected to a graphitization process and then a crushing process. The particle diameter D of these carbon nanotubes is 50In another aspect of the carbon nanotubes according to the present embodiment, the carbon nanotubes are obtained by subjecting carbon nanotube powder or carbon nanotube granules to a pulverization treatment and then graphitizing the pulverized carbon nanotubes. Although the reason why the present embodiment can reduce metal impurities and obtain carbon nanotubes with excellent dispersibility is not entirely clear, the present inventors speculate as follows.

[0014] First, the reason why metal impurities can be reduced is that the CNTs have been graphitized. The graphitization is a heat treatment at a high temperature of, for example, 2000°C or higher, and the metal impurities (catalytic metals) derived from the catalyst mixed in the CNTs can be removed by the graphitization. In contrast, other methods for removing the metal impurities derived from the catalyst mixed in the CNTs include (i) a method of immersing the CNTs in an acidic solution containing at least one of sulfuric acid, hydrochloric acid, and hydrofluoric acid to dissolve and remove the metal, or (ii) a method of converting the metal impurities into metal oxides by irradiating the CNTs with microwaves, thereby converting them into metal oxides that are inactive at the operating voltage of the secondary battery and are not dissolved in the electrolyte. Among these, the acid treatment method (i) leaves acid ions on the CNT surface even if heat treatment (less than 600°C) is performed after pickling, so there is a risk of corrosion of the positive electrode material, and it may also damage the CNTs and cause lattice defects. In addition, since the surface of the catalytic metal is covered with a graphite layer, the acid solution alone cannot completely dissolve and remove the catalytic metal because the graphite layer prevents the acid solution from reaching the catalytic metal. Furthermore, the microwave irradiation method (ii) above has the problem that the CNTs are oxidized, decreasing the electrical conductivity of the CNTs. In this way, the method of graphitizing CNTs is optimal as a method for removing metal impurities (catalytic metals) derived from catalysts that are mixed in with the CNTs.

[0015] On the other hand, when the CNT is graphitized, the crystallization of the CNT proceeds, and there is a problem that the dispersibility in the resin is reduced. However, in this embodiment, the CNT is pulverized before or after the graphitization to be fine powder, or the CNT that is already fine powder is graphitized. Then, by being made into fine powder in this way, the dispersibility of the CNT in the resin is improved. Therefore, the inventors speculate that the carbon nanotube according to this embodiment can reduce metal impurities and has excellent dispersibility.

[0016] (Graphitization treatment) The graphitization treatment in this embodiment is a heat treatment at a temperature of 2000° C. or higher and 3000° C. or lower in a non-oxidizing atmosphere. More specifically, the graphitization process is carried out by heating and holding the CNTs at 2000°C or higher in an oxygen-free atmosphere (for example, in a nitrogen stream, in a vacuum, or in carbon powder (also known as packing powder, and usually coke powder or CB is used)). In this case, the presence of oxygen in the atmosphere reduces the yield of CNTs obtained, so it is desirable to keep the oxygen concentration in the atmosphere at 1% by volume or less. When this graphitization process is carried out on a large scale, it is advantageous to use an Acheson-type electric furnace. On the other hand, when it is carried out on a small scale, a specified amount of CNTs can be filled into a graphite pipe, which is then embedded in carbon powder, and an alternating current is passed through both ends of the pipe. Thus, in the graphitization process, it is preferable to heat the CNT to 2000°C or more and 3000°C or less, more preferably to heat to 2500°C or more and 2900°C or less, and particularly preferably to heat to 2700°C or more and 2900°C or less. When heated in such a temperature range, the crystallites of the CNT are rearranged and the shape changes, the wire diameter becomes slightly smaller, but the crystallinity grows. In addition, the higher the processing temperature, the more the functional groups or metal impurities on the surface can be reduced. However, it is thought that the higher the processing temperature, the stronger the entanglement of the primary aggregates or secondary aggregates that existed in the CNT before graphitization becomes due to the heat treatment, and the worse the dispersibility when mixed with resins, etc.

[0017] (Crushing process) The pulverization process in this embodiment includes dry pulverization and wet pulverization, which can be used depending on the purpose. The reason why the dispersibility of the graphitized CNT decreases is believed to be that the complex and strong entanglement of the CNT fibers cannot be disentangled by a normal dispersing machine or dispersion method. In order to disentangle the strong entanglement, it is preferable to use a powerful pulverization means. In this embodiment, it is preferable to use dry grinding. In the case of dry grinding, the grinding machine to be used varies depending on the target particle size and particle size distribution. For example, when the target is fine grinding to tens of μm or less, a jet mill, a pin mill, a vibration ball mill, or a planetary mill is used. Among grinding machine manufacturers, jet mill type grinding machine manufacturers include Seishin Enterprise Co., Ltd., Aisin Technologies Co., Ltd., and Earth Technica Co., Ltd. Furthermore, pin mill manufacturers include Makino Sangyo Co., Ltd., Nishimura Machinery Manufacturing Co., Ltd., and Hosokawa Micron Co., Ltd. Furthermore, impeller mill manufacturers include Seishin Enterprise Co., Ltd., and Earth Technica Co., Ltd.

[0018] (CNT particle size) The particle diameter D of the carbon nanotube according to this embodiment 50 In addition, when the carbon nanotubes according to the present embodiment are carbon nanotube powders that have been subjected to a graphitization treatment, the particle diameter D 50 is preferably 100 μm or less. The particle size distribution of CNTs is measured by the laser diffraction / scattering method defined in ISO13320. The measurement was performed using a Laser Micron Sizer LMS-3000 (manufactured by Seishin Enterprise Co., Ltd.). The measurable range of this device is 0.01 to 3500 μm. The aqueous dispersion medium was prepared by adding 0.05 g of polyoxyethylene alkyl ether (Kao Corporation, product name Emulgen 705) as a surfactant to 50 mL of pure water. For the measurement, 10 mg of CNTs were weighed into a 20 mL vial, 10 mL of aqueous dispersion medium was added, and the CNTs were dispersed for about 10 minutes using an ultrasonic disperser. The optical model of the measurement was set to the refractive index of 1.520 for CNTs and 1.333 for water, respectively, for the measurement. CNT optimum particle size D 50 is 10 μm or more and 100 μm or less, and preferably 10 μm or more and 50 μm or less. If it is larger than 50 μm, many aggregates will be present and dispersibility will be poor. In addition, a process to make it finer than 10 μm is a process to cut the CNT fibers, which is not preferable because it will deteriorate the conductivity.

[0019] (Raw material CNT) The fiber diameter of the CNTs used as raw materials is 0.3 nm, which is the diameter that can be produced with current technology, but it can be thinner than 0.3 nm. As the fiber diameter increases beyond 50 nm, the electrical and mechanical properties tend to decrease, and as the diameter increases beyond 100 nm, the advantage over CB or carbon nanofibers tends to disappear. Furthermore, in this embodiment, from the viewpoint of the CNTs efficiently forming a three-dimensional network, the fiber diameter of the CNTs is more preferably 3 nm or more and 50 nm or less, even more preferably 5 nm or more and 40 nm or less, and particularly preferably 10 nm or more and 30 nm or less. The fiber length of CNT is related to electrical conductivity, mechanical properties, or dispersibility. The fiber length of CNT is preferably 0.1 μm or more and 2000 μm or less, and more preferably 1 μm or more and 1000 μm or less. As the fiber length becomes smaller, there is a tendency that it becomes difficult to express electrical conductivity or mechanical properties, and as the fiber length becomes larger, the entanglement of the fibers becomes stronger, and not only does it increase the number of poorly dispersed lumps, but it also increases the number of fiber breaks during kneading and dispersion, which is undesirable. The aspect ratio of CNT is about 10 to 10,000. In addition, as the CNT, a structure in which a hexagonal mesh graphite sheet is formed into a cylindrical shape is preferably used. The CNT may be either a single-layer CNT or a multi-layer CNT, and can be selected according to the final purpose. In addition, there is no limitation regarding the manufacturing method of CNT. Examples of the manufacturing method of CNT include a pyrolysis method in which a carbon-containing gas is brought into contact with a catalyst, an arc discharge method in which an arc discharge is generated between carbon rods, a laser evaporation method in which a carbon target is irradiated with a laser, a CVD method in which a carbon source gas is reacted at high temperature in the presence of metal fine particles, and a HiPco method in which carbon monoxide is decomposed under high pressure. In addition, the CNT may be doped with metal atoms.

[0020] [Carbon nanotube resin composition] Next, the carbon nanotube resin composition according to this embodiment will be described. The carbon nanotube resin composition according to this embodiment contains the above-mentioned carbon nanotubes and a resin. The carbon nanotubes according to this embodiment can reduce metal impurities and have excellent dispersibility, so that the carbon nanotubes according to this embodiment can be used to produce a carbon nanotube resin composition that is useful as a constituent material for lithium ion secondary batteries.

[0021] Examples of the resin include polyolefin resin, polyhalogenated olefin resin, polyester resin, polyamide resin, polyimide resin, polyether resin, polyvinyl resin, polystyrene resin, polyvinyl alcohol resin, polymethacrylate resin, polyurethane resin, polyepoxy resin, polyphenol resin, polyurea resin, and polyethersulfone resin. EXAMPLES

[0022] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" are by weight unless otherwise specified.

[0023] [Preparation Example 1] A graphitization treatment device was prepared in which electrodes were attached to both ends of a hollow graphite pipe with an inner diameter of 4 cm and a length of 100 cm, and the pipe could be directly heated by passing an alternating current. In this graphitization treatment device, about 15 g of "K-Nanos-100T", a pelletized CNT granule manufactured by Kumho Petrochemical Co., Ltd., was packed in a cylindrical graphite container with an inner diameter of 3 cm, an outer diameter of 3.5 cm, and a length of 10 cm, and then inserted into the graphite pipe at approximately the center, after which nitrogen gas was introduced into the inside of the graphite pipe. Then, an alternating current was passed through the graphite pipe, and the pipe was subjected to a heat treatment (graphitization treatment) at a temperature of 2000°C for 30 minutes to produce graphitized CNT.

[0024] [Preparation Example 2] Graphitized CNTs were produced in the same manner as in Preparation Example 1, except that the graphitization temperature was changed to 2500°C.

[0025] [Preparation Example 3] Graphitized CNTs were produced in the same manner as in Preparation Example 1, except that the graphitization temperature was changed to 2900°C.

[0026] [Preparation Example 4] "K-Nanos-100T", a pelletized CNT granule manufactured by Kumho Petrochemical Co., Ltd., was prepared and pulverized using a jet mill "PJM-80" manufactured by Nippon Pneumatic Co., Ltd. to produce pulverized CNT. Thereafter, graphitized CNTs were produced in the same manner as in Preparation Example 1, except that the pulverized CNTs were used instead of the CNT granules and the graphitization temperature was changed to 2900°C.

[0027] [Preparation Example 5] We prepared "K-Nanos-100P," a CNT powder manufactured by Kumho Petrochemicals. Thereafter, graphitized CNTs were produced in the same manner as in Preparation Example 1, except that this CNT powder was used instead of the CNT granules and the graphitization temperature was changed to 2900°C.

[0028] [Example 1] The graphitized CNTs obtained in Preparation Example 3 were pulverized using a jet mill "PJM-80" manufactured by Nippon Pneumatic Co., Ltd. to produce graphitized and pulverized CNTs. The production conditions for CNTs are as shown in Table 1 below. The obtained CNTs were mixed at 2% into polypropylene resin (Prime Polymer's "J229E") and mixed at 210°C for 4 minutes using a Plastomill to create a resin composition.

[0029] [Examples 2 to 5, Comparative Examples 1 to 3, and Reference Examples 1 and 2] According to the production conditions shown in Table 1, CNTs and resin compositions were produced in the same manner as in Example 1, except that each CNT was subjected to each treatment.

[0030] [Evaluation of CNTs and resin compositions] The properties of the CNTs and the resin composition (ash content, dispersibility, particle size) were evaluated by the following methods. The results are shown in Table 1. (1)Ash content The ash content of the CNTs was measured in accordance with JIS K-6218-2 (ASTM D-1506). Specifically, the sample was placed in a porcelain crucible and completely incinerated at 750°C or 825°C, and the ash content (unit: %) was calculated from the amount of residue after the sample was completely incinerated. The ash content indicates the progress of the graphitization process, with the lower the ash content, the more progressed the graphitization process is. It can also be said that the lower the ash content, the fewer metal impurities there are in the CNTs. (2) Dispersibility The dispersibility of the resin composition was evaluated by melt pressing the resin composition to prepare a thin piece, and observing the thin piece using transmitted light through a microscope (magnifications of 50x and 200x). The degree of dispersion was evaluated in the range of 0 to 10. The larger the value, the better the dispersibility. The photograph of the observation is shown in FIG. 1. (3) Particle size D 50 The particle size distribution of CNTs was measured by the laser diffraction / scattering method defined in ISO 13320. The measuring device used was a Laser Micron Sizer LMS-3000 (manufactured by Seishin Enterprise Co., Ltd.). From the obtained particle size distribution, the particle size D 50 The value of was obtained.

[0031] [Table 1]

[0032] The results shown in Table 1 reveal the following: It was found that the amount of metal impurities, as measured from the ash content, was reliably reduced by graphitization at 2000°C, 2500°C, or 2900°C. Although 2000°C is a temperature higher than the melting point (1535°C) of iron impurities, which constitute the metal impurities, the amount of impurities was not significantly reduced. On the other hand, it was found that the dispersibility when blended into polypropylene resin was extremely deteriorated by heating at high temperatures (see Comparative Examples 1 to 3). The inventors speculate that the reason for the poor dispersibility is as follows. The CNT granules were produced by compression granulation (roller compactor method or briquette machine method), and therefore the secondary agglomerates on the order of microns are thought to be strongly intertwined.In addition, the graphitization treatment was carried out at 2000°C or higher (especially 2500°C or higher), which completely eliminated the various functional groups that were present in small amounts on the CNT surface, and also eliminated the reactive active sites that were present in the disordered crystallites due to the development of the crystallites.Furthermore, the bonds of the agglomerates that had been strengthened by mechanical compression were further strengthened by the heat treatment, which is thought to have made them difficult to disperse.

[0033] The CNTs obtained in Example 1 were subjected to a pulverization treatment after graphitization. Although the pulverization treatment significantly improved the dispersibility, it did not reach the level of the raw CNTs before graphitization (see Reference Example 2, Comparative Example 3, and Example 1). The CNTs obtained in Example 2 were subjected to a graphitization treatment after a crushing treatment. It was found that the dispersibility was better than that of Example 1 (see Examples 1 and 2). The CNTs obtained in Example 3 were obtained by further pulverizing the CNTs obtained in Example 2. The dispersibility was the best among the graphitized products using CNT granules as the raw material, and was close to that of the raw CNTs (see Reference Example 2 and Example 3). However, although not measured this time, jet mill pulverization was performed twice, so it is assumed that the CNT fibers were cut. The CNTs obtained in Example 4 were obtained by graphitizing CNT powder. It was found that the dispersibility was far superior to that of a CNT granule that had been graphitized at 2900°C, and was almost equivalent to that of a CNT granule that had been graphitized at 2900°C after being pulverized (see Comparative Example 3, and Examples 2 and 4). The CNTs obtained in Example 5 were obtained by further subjecting the CNTs obtained in Example 4 to a pulverization treatment. The dispersibility was at a level almost equivalent to that of the raw CNTs (see Reference Examples 1 and 2, and Example 5). [Industrial Applicability]

[0034] The carbon nanotubes of the present invention are useful as a constituent material for paints, inks, resin molded products, and the like, and are particularly useful as a conductive assistant in electrode mixtures for lithium ion secondary batteries.

Claims

1. Carbon nanotubes that have been subjected to a graphitization process and then a crushing process, The particle diameter D of the carbon nanotube 50 is 100 μm or less, Carbon nanotubes.

2. The carbon nanotube powder or the carbon nanotube granules are pulverized and then graphitized. Carbon nanotubes.

3. The carbon nanotube according to claim 2, The particle diameter D of the carbon nanotube 50 is 100 μm or less, Carbon nanotubes.

4. A composite material comprising the carbon nanotubes according to any one of claims 1 to 3 and a binder resin. Carbon nanotube resin composition.

Citation Information

Patent Citations

  • Composite material and molded article

    CN105121339A

  • Carbon nanotube

    JP2003261311A

  • Composite material

    JP2007254886A

  • Method for improving conductivity of resin molded body comprising carbon nanotube by heat treatment

    JP2009074072A

  • Method for manufacturing resin molded article containing fine carbon fiber localized on surface layer by transferring process

    JP2009255568A

Cited By

  • Carbon nanotubes and carbon nanotube resin composition

    WO2026154647A1